TIME DEIXIS IN ANTHONY MCCARTEN’S SCREENPLAY THE THEORY OF EVERYTHING - Johan Ardian Putra; M. Manugeren (Universitas Islam Sumatera Utara, 2022)
This research is about time deixis on the screenplay of The Theory of Everything by Anthony McCarten with various indicators that explain the whole analysis, such as multiverse concepts in the physics law that are in force. The lack of understanding of language and time deixis is a serious problem often creating chaos in human civilization, resulting in something very extraordinary bad impact on life that seems to have nothing to do at all. This research is useful to make humanity aware of the importance of understanding language and understanding pluralism as a new era of human, not only in culture but also the way to learn. In the fact, that has small probability of success to rebel it off since it involves the prosperity of human life throughout the world. However, this study does not aim to force readers to change the ideology, perspective, and point of view that have been believed, only as the informative research showing new concepts of understanding literary work and life concepts so far. Notwithstanding, political interests in the future may be able to restructure all policies that have been mutually agreed internationally, if the agreement is nearing a saturation point. The method used in this study is a scientific methodology with qualitative description by collecting data through the screen play and literary review. And, various historical and future suggestions are also presented in this study. The results show that there are exposures of time deixis in the screenplay: ambiguity, polysemy, and vagueness.